The efficacy of plant extracts on cecal amebiasis in rats (Veterinary Science Development, 2015)
Amebiasis caused by Entamoeba histolytica is a major public health problem in tropical and subtropical countries. Treatment failure with specific chemotherapy has been reported suggesting the possibility of drug resistance. This study investigated the anti-amoebic effects of four plant extracts on cecal amebiasis in rats. The cecal amebiasis was induced by the injection of 3.0×105 troph/mL of E. histolytica parasite directly into the rat’s caecum. A total of 137 rats were used for these studies; five rats in each group for both positive and negative control, 15 rats in each group to test the four plant extracts and metronidazole. The infected rats were treated for cecal amebiasis using each of the four plant extracts at graded doses of 100 mg/kg, 200 mg/kg and 400 mg/kg and with metronidzole at a dose of 62.5 mg/kg,100 mg/kg and 125 mg/kg for five consecutive days. The efficacy of the four plant extracts were evaluated based on Neal’s, 1951 method. The plant extracts of Garlic, Guava, Pawpaw and Pumpkin at 400 mg/kg and 200 mg/kg body-weight gave a cure rate of 80%, 100%, 60%, 40% and 40%, 80%, 40%, 0%, respectively. The mean parasite count in the cecal contents of the treated rats at a dose 400 mg/kg were 18.5±1.6, 0.0±0.0, 33.3±1.8 and 49.5±4.0, respectively. The difference was statistically significant (P